On Memories and Ambiguities: Ernesto Sábato and the Concept of “Absolute Innocents” as a Representation of Argentina’s Dictatorial Past - Angelone, Juan Pablo (2023)
As president of the Movement for the Recovery of Disappeared Children in the final years of the Argentine dictatorship, as well as in his public function as president of CONADEP from 1983 to 1984, Ernesto Sabato introduced the term "absolute innocents." Initially, he referred to the kidnapped newborn children and then to the disappeared young people. Inscribing the notion of "absolute innocents" in the framework of the reflection on victims of historical massacres and/or genocides and interrogating Sabato's thought on state terrorism, revolutionary violence, and the disappeared, we can affirm that the notion of "absolute innocents" constitutes a representation of the dictatorial past differentiated from the "theory of the two demons." However, it implies, in turn, a "forgetting" of the political identities of the disappeared individuals, especially of those who were members of political-military organizations.